EDUKASI PEMBERIAN SARI KACANG HIJAU (VIGNA RADIATE) SEBAGAI UPAYA PENINGKATAN PRODUKSI ASI PADA IBU NIFAS - Naimah Nasution; Kristin Natalia; Septa Dwi Insani; Juliana Sion Sihombing (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Exclusive breastfeeding refers to the practice of providing breast milk solely to infants aged 0-6 months without introducing any additional solid foods or liquids such as formula, fruit juice, honey, or tea. The objective of this study is to assess the impact of administering green bean juice (Vigna Radiate) on enhancing postpartum breast milk production among mothers receiving care at the Yeni Clinic in the Tinggi Raja District, Asahan Regency, in the year 2022. This research follows a quantitative approach and employs a quasi-experimental design known as the "slum experiment," involving both pre-test and One Group post-test designs. Data analysis involved the application of a paired t-test on a sample of 10 postpartum mothers facing challenges in providing exclusive breastfeeding, and the study was conducted in June 2022. The findings of the study indicated that prior to the introduction of green bean extract, the majority of mothers (90%) experienced low breast milk production, with only one mother (10%) achieving sufficient breast milk production. Following the reintroduction of green bean extract, two mothers (20%) observed an increase in breast milk production, while eight other mothers (80%) achieved adequate breast milk production. Data analysis results revealed a p-value of 0.000, which is less than 0.005, indicating a significant influence of administering green bean juice (Vigna Radiate) on breast milk production among postpartum mothers at the Yeni Clinic, Tinggi Raja District, Asahan Regency, in 2022.